The Total Amount of Leukocytes in the Blood of Astrakhan Sheep and Changes in the Immune System Depending on the Seasons and Nutritional Conditions - B. M. Bazarov, Z. T. Rajamuradov ,M. Sh. Ismoilov (International Journal of Advanced Science and Technology, 2020)
The article describes the dynamics of changes in the blood of leukocytes and the immune system in the blood of karakul ewes depending on the seasons. The amount of biochemical components in the blood of Karakul sheep has been found to vary depending on the seasons, feeding conditions and physiological conditions. The variability of leukocytes and the immune system was clearly manifested in the body of ewes in winter and spring, as it was found that this condition occurs as a result of lack of nutrients in the diet of ewes. It is important in determining the ratio of leukocytes in the blood, making a diagnosis and predicting their productivity.